Al-Qur'an as a true report and source of knowledge in the early Malay intellectual tradition - Elias @ Mayah, Aliza; Jusoh, Che' Razi (2015)
This paper aims to highlight the scholarly discussion in a few early Malay kitab on one of the most allusive epistemological issues of ‘how do we know what we know” and to expound its paramount importance and bearing in our contemporary life. It attempts to analyze the holistic approach towards the Qur’an as a source of knowledge by firstly addressing, rather than avoiding, the more fundamental and prior issue of the causes or means of knowledge and establishing it as being the most indubitable true report. By so doing, the paper hopes to be able to suggest and insist that this approach be revived in order to equip Muslims with the right defensive knowledge and boost their confidence in facing the growing confused and skeptical world of today.